The Effect of Brand Image and Islamic Branding Towards Purchasing Decision: The Role of Brand Awareness as a Mediation Variable - Fifi Septiani; Rozikan Rozikan (Telaah Bisnis, 2024)
The increasingly fierce competition in the business world has led manufacturers to have marketing strategies that can enhance consumer interest in making purchasing decisions. Fashion is considered to have great potential, especially for Muslim fashion products. This study aims to determine the influence of brand image and Islamic branding on the purchasing decisions of Muslim consumers on Rabbani products, mediated by brand awareness. The sample in this study consisted of female students from Muhammadiyah University of Yogyakarta who had purchased Rabbani products. The total number of samples used was 206 respondents. The method used to collect samples was purposive sampling. This study used primary data obtained from distributing online questionnaires through Google Forms. The data obtained were analyzed using SmartPLS 3.0. The results of the study showed that brand image and Islamic branding have a positive effect on brand awareness. The study also showed that brand awareness has a positive effect on purchasing decisions. Brand awareness mediates the relationship between brand image and Islamic branding on purchasing decisions. The results of this study can serve as a reference for Rabbani product companies in leveraging brand image and Islamic branding aspects to create good brand awareness for consumers, ultimately enhancing purchasing decisions.